Absorption Wavelength Extension for Dye-Sensitized Solar Cells by Varying the Substituents of Chiral Salen Cu(II) Complexes - Shoji, Ryosuke; Shun Ikenomoto, Shun Ikenomoto; Sunaga, Nobumitsu; Sugiyama, Mutsumi; Akitsu, Takashiro (Journal of Applied Solution Chemistry and Modeling, 2016)
New chiral salen-type Cu(II) complexes (1-9) were prepared, and the effects of different substituent groups on their absorption spectra were evaluated using time-dependent density functional theory (TD-DFT). Electron withdrawing groups resulted in a red-shift and an increase in the peak intensity. According to cyclic voltammetry analyses, the introduction of electron withdrawing groups brought the redox potentials (E0) in agreement with the orbital level energies determined via TD-DFT. The reduction potentials for 1-9 are less than âˆ’0.500 V, and therefore, it is electrochemically possible to dope electrons in TiO2. In addition, the oxidation potentials are greater than +0.200 V, indicating that it is electrochemically possible to regenerate the dyes. Preproduction dye-sensitized solar cells (DSSCs) fabricated using compounds 1-9 generated electricity. In particular, the DSSC prepared using 2 (which has electron withdrawing groups and the largest maximum absorption) exceeded the power conversion efficiency of DSSC fabricated using N3, which is a commonly used Ru(II) complex.